Early identification and intervention for children with initial signs of reading deficits - A blinded randomized controlled trial. (February 2019) - Volkmer, Susanne; Galuschka, Katharina; Schulte-Körne, Gerd
Abstract: Early identification of reading disorder (RD) can prevent a "wait-to-fail" situation and can increase the efficacy of subsequent interventions. In this study we identified children in the middle of first grade of German elementary schools who were at risk for RD and evaluated a subsequent phonics intervention. We assessed 234 children and randomly allocated those performing below the 30 th percentile in a short standardized reading speed test to a six-week phonics (n = 29) or blinded motor control intervention (n = 26). Both interventions were implemented at school three times a week in small groups. Results showed that the first graders who had received the phonics instruction improved significantly in reading ability compared to the control group. Moreover, significantly more children in the control group exhibited RD than in the phonics group. This study provides the basis for developing school-based early identification and intervention programmes to remediate reading deficits and prevent RD. Highlights: Reading speed enables identification of German-speaking first-graders at risk of RD. High frequency school-based phonics intervention improved reading. Phonics intervention reduced the number of children with RD by the end of first grade. The study shows the value of school-based early identification and intervention models.